Potential of Vicenin-2 in Chitosan Encapsulated Basil (Ocimum sanctum Linn.) Leaf Extract as A Therapeutic Alternative Medicine for Non-small cell carcinoma lung cancer - Alvian Mohamad Yapanto (Lembaga Pengembangan Kinerja Dosen, 2022)
This study aimed to analyze the production of chitosan-encapsulated vicenin-2 extracted from basil leaves and its effect on non-small cell carcinoma lung cancer. Vicenin-2 Extract from Chitosan-Encapsulated basil (Ocimum sanctum Linn.) leaf extract is produced by library research and laboratory practice. In non-small cell carcinoma lung cancer, vicenin-2, one of the components in basil leaves, and chitosan capsules, which are deacetylated chitin, had a substantial anticancer effect. It is required to investigate the effectiveness and safety of basil leaf powder containing mostly vicenin-2 and encapsulated in chitosan capsules.